Pengaruh Minat Beli, KepePengaruh Minat Beli, Kepercayaan, dan Pengalaman Konsumen Terhadap Kepuasan Konsumen (Studi Kasus Pada “Catering Kami” Kecamatan Medan Helvetia) - Nasution, Doly Anwar; Rahma, Tri Inda Fadhila; Jannah, Nurul (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This research aims to determine the influence of consumer buying interest, consumer trust, consumer experience on consumer satisfaction with our catering. This research is quantitative research. The data used comes from direct consumers (primary data). The analysis used in this research is multiple linear regression analysis, and processed using the SPSS Version 22.0 program. The research results show that: 1) The research results show that consumer buying interest based on testing the research hypothesis is Ha accepted and H0 rejected. This explains that partially consumer buying interest influences consumer satisfaction with our catering. 2) The results of the research show that consumer confidence based on testing the research hypothesis is that Ha is accepted and H0 is rejected. This explains that partially consumer trust has an influence on consumer satisfaction with our catering. 3) The results of the research show that consumer experience based on testing the research hypothesis is that Ha is rejected and H0 is accepted. This explains that partially consumer interest in experience has no effect on consumer satisfaction with our catering.